Synergizing Technological Innovation, Quality Management, and Inclusivity in Transforming Industry Responsive Technical and Vocational Education and Training TVET - Abdul Habib Arrasyidi Desky; Nizwardi Jalinus; Ernawati Ernawati; Fadhilah Fadhilah; T Taali; Yulia Fitri Ananda (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
This study aims to explore the synergy between technological innovation, quality management, and inclusivity strategies in transforming Technical and Vocational Education and Training (TVET) to become more responsive to industry needs in the digital era. A descriptive qualitative approach was employed through interviews, participatory observations, and document analysis in several TVET institutions. The findings indicate that the use of technology, such as Learning Management Systems (LMS) and digital simulations, enhances learner engagement and improves the effectiveness of teaching and learning processes. However, limited teacher training and technological infrastructure remain major challenges. The implementation of systematic quality management, including data-based evaluation and strategic planning, was found to support curriculum alignment with industry requirements. Inclusivity strategies through adaptive learning and individualized support also demonstrated positive impacts for learners, including those with special needs. Collaboration with industry through internships and project-based learning further strengthens graduates’ work readiness, although its implementation is not yet evenly distributed across institutions. Overall, this study confirms that the synergy of technology, quality management, and inclusivity forms an essential foundation for realizing adaptive, industry-responsive, and equitable vocational education amidst technological advancement and the dynamics of the 21st-century labor market.